GEOPOLÍTICA E SUSTENTABILIDADE: UM ESTUDO SOBRE A INFRAESTRUTURA DE SANEAMENTO BÁSICO NA FRONTEIRA INTERNACIONAL BRASIL-BOLÍVIA - LEANDRO DOS SANTOS PEREIRA (2023)
The present study aimed to investigate the basic sanitation infrastructure in the Brazil-Bolivia border region polarized by Corumbá-MS. It was based on the assumption that basic sanitation is a set of essential infrastructures and services to guarantee the salubrity of environments and, therefore, the health of the population. The methodology used was divided into three moments. The first consisted of a survey of the literature on basic sanitation; the second involved document consultation, organization of spatial data made available on the official websites of public authorities of different geographic scales (municipal, state and federal) and the third moment consisted of carrying out fieldwork for observation, recording and application of a questionnaire on the degree of satisfaction of residents of Corumba with regard to sanitation services. The socio-spatial cut that served as the basis for carrying out the survey was the Cristo Redentor neighborhood, located in the upper part of the city space in Corumba. Finally, the interpretative model that was adopted for the development of the discussions was based on theories of Geopolitics and Political Geography in a critical perspective and socio-historical approach, since basic sanitation is, in short, a territorial policy of the most essential, but which faces several challenges, whether due to the fragility of government actions or the lack of resources to provide infrastructure. Given this, it is important that basic sanitation is a constant concern of society and governments. Only in this way will it be possible to guarantee the health and well-being of people and the sustainable development of the country. Keywords: Basic sanitation; Infrastructure; Border; Sustainability; Geopolitics.